Inverse emulsion polymerization‐assisted designing of superparamagnetic poly (2‐hydroxyethyl methacrylate) nanoparticles and magnetically triggered release of cisplatin. Issue 5 (15th February 2021) - Gupta, Meher Kanta; Bajpai, Jaya; Bajpai, Anil Kumar
Abstract: Superparamagnetic nanocarriers of poly (2‐hydroxyethyl methacrylate) (PHEMA) were prepared by carrying out benzoyl peroxide (BPO) initiated inverse emulsion‐free radical polymerization of HEMA in the presence of poly (vinyl alcohol) (PVA) and subsequent in situ precipitation of magnetite within the PHEMA matrix. The as‐prepared nanoparticles were characterized by FTIR and UV–visible spectroscopy, vibrating sample magnetometry (VSM), particle size and zeta potential analysis, and transmission electron microscopy, respectively. The PHEMA nanocarriers were investigated for their blood compatibility, and cytotoxicity response to L929 cells. The superparamagnetic nanoparticles were loaded with an anticancer drug cisplatin and the release profiles of the drug were examined as a function of various experimental parameters like composition of the PHEMA nanocarriers, percentage of drug loading, and strength of the externally imposed magnetic field. The kinetics of the drug release process was also investigated, and the obtained release data were applied to different mathematical kinetic models to explore the nature of the release mechanism. Abstract :